miR-939-3p induces sarcoma proliferation and poor prognosis via suppressing BATF2 - Xu, Wanwen; Huang, Yinghui; Lei, Zengjie; Zhou, Jie (Frontiers in Oncology, 2024)
Background: Sarcoma is a rare and aggressive malignancy with poor prognosis, in which oncogene activation and tumor suppressor inactivation are involved. Accumulated studies suggested basic leucine zipper transcription factor ATF-like 2 (BATF2) as a candidate tumor suppressor, but its specific role and mechanism in sarcoma remain unclear.The expression levels of BATF2 and miR-939-3p were evaluated by using human sarcoma samples, cell lines and xenograft mouse models. Bioinformatics analysis, qPCR, Western blot, cell proliferation assay, overexpression plasmid construction, point mutation and dual luciferase reporter assay were utilized to investigate the role and mechanism of miR-939-3p in sarcoma.In this study, we demonstrated that the expression of BATF2 was downregulated in human sarcoma tissues and cell lines. The downregulation of BATF2 was negatively associated with the prognosis of sarcoma patients. Subsequent bioinformatic prediction and experimental validations showed that BATF2 expression was reduced by microRNA (miR)-939-3p mimic and increased by miR-939-3p inhibitor. Additionally, miR-939-3p was upregulated in sarcoma tissues and cells, correlating with a poor prognosis of sarcoma patients. Moreover, miR-939-3p overexpression suppressed sarcoma cell proliferation, which was significantly attenuated by the restoration of BATF2, while siRNA-mediated knockdown of BATF2 aggravated the miR-939-3p-induced promotion of sarcoma cell proliferation. Further computational algorithms and dual-luciferase reporter assays demonstrated that miR-939-3p repressed BATF2 expression via directly binding to its 3' untranslated region (3' UTR).Collectively, these findings identified miR-939-3p as a novel regulator of BATF2, as well as a prognostic biomarker in sarcoma, and revealed that suppressing miR-939-3p or inducing BATF2 expression may serve as a promising therapeutic strategy against sarcoma.